Association between relative telomere length and a genetic variant of SIRT1 gene and age-related macular degeneration - L.K. Moshetova; O.P. Dmitrenko; O.I. Abramova; N.S. Karpova; K.I. Turkina; I.N. Saburina (РМЖ "Клиническая офтальмология")
L.K. Moshetova1, O.P. Dmitrenko2, O.I. Abramova1, N.S. Karpova2, K.I. Turkina1, I.N. Saburina2,3 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2Research Institute of General Pathology and Pathophysiology, Moscow, Russian Federation 3Research Institute of Molecular and Personalized Medicine, Moscow, Russian Federation One of the most important factors predisposing to the development of age-related macular degeneration (AMD) is aging. Telomeres are important for aging by maintaining genome stability. Aim: to identify the association between relative telomere length of buccal epithelial cells and SIRT1 rs12778366 genetic variation and late AMD. Patients and Methods: 100 patients (200 eyes) were enrolled, i.e., 50 patients with AMD (AREDS category 4) and 50 patients without AMD. Genomic DNA isolated from buccal epithelial cells by phenol-chloroform extraction was used. Genotyping of SIRT1 rs12778366 polymorphic locus was performed by TaqMan® real-time PCR. Telomere length was measured by real-time PCR as described earlier [Cawthon, 2002] using specific primers. Relative telomere length was assessed by the relative telomere to single-copy gene (T/S) ratio. Results: the rate of allele C was 25% in the study group and 14% in the control group (p=0.049). The rate of heterozygotic TC genotype was twice higher in the study group compared to the control group (p=0.045). In heterozygotic carriers of the allele C of the SIRT1 rs12778366 gene, the risk of AMD is 2.048- and 2.425-times higher in сodominant and dominant inheritance pattern, respectively. In patients with late AMD, there are more short telomeres (64% vs. 48% in the control group, р=0.0002). Conclusions: further studies of a polymorphic SIRT1 gene locus in the association with telomere length in a larger sample are required. In the future, these molecular markers can be applied to predict the individual course of AMD and to implement preventive measures. Keywords: age-related macular degeneration, relative telomere length, rs12778366, SIRT1 gene, age-related diseases, buccal epithelium, genetic testing. For citation: Moshetova L.K., Dmitrenko O.P., Abramova O.I. et al. Association between relative telomere length and a genetic variant of SIRT gene and age-related macular degeneration. Russian Journal of Clinical Ophthalmology. 2021;21(3):143–146 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-143-146.